Estudio de factibilidad para la creación de un parque tecnológico para el procesamiento de productos cárnicos, alimenticios, parroquia Viva Alfaro, cantón Quevedo, año 2014. - Plaza Ortega, Alex Fabián (2015)
This feasibility study for the creation of a technology park for processing meat, food, parish Live Alfaro products, Canton Quevedo, it has been done according to the technical requirements and the needs of potential customers. It is referring to contextual framework of the investigation, where an analysis of the current situation of the problem is included, through a diagnosis that allows the formulation and systematization of the problem, objectives, assumptions and justification arise; then the theoretical framework where the most relevant information related to the research objectives outlined is built; methods, types, techniques, sources of information, and with their respective populations are identified source; then the results found by a market study which identified the existing unsatisfied demand for a technology park for food processing meat products is presented. The technical study identified the optimal location, machinery, equipment, infrastructure, raw materials, supplies and labor required for the operating process plant; in the economic study the feasibility of investment was demonstrated by an analysis of the revenue and expenditure of the project; financial assessment through indicators such as NPV and IRR demonstrated the feasibility and economic viability of the project; finally the conclusions and relevant recommendations.